Cell site analysis: Roles and interpretation. Issue 5 (September 2019) - Tart, Matt; Pope, Sue; Baldwin, David; Bird, Robert
Highlights: Analysts and experts have varying skills, knowledge and understanding. The word "interpretation" is used inconsistently, causing confusion. These affect a practitioner's ability to reliably answer questions. The differences between presentation, explanation and interpretation are outlined. Recommendations on the roles of different types of practitioner are made.